(untitled) (Bangladesh Journal of Medical Science, 2018)
Background and objective: One of the suggested ways of financing health care is health insurance combined with general taxation. This study aimed to assess the willingness to pay for health insurance among the adult population and the factors thereof. Methods: A multi-stage cluster sampling with cross sectional study design was adopted to select the respondents. Data was collected by face to face interview. A total of 1018 data was analyzed with response rate of 84.3%. The data on willingness to pay for insurance was collected using the contingent valuation method with bidding style. Data entry and analysis was done by SPSS 22.0 version. A p-value of less than 0.05 was considered as statistically significant. Results: Data analysis revealed that about half (46.7%) of the respondents agrees to pay monthly health insurance premium. Among those who were unwilling to pay, 81.3% were unable to afford the monthly insurance. Logistic regression analysis revealed that occupation, level of education, gender, marital status, monthly family income and treatment preference appeared to be potential predictors for willingness to accept health insurance (p<0.05). Recommendation: The key policy priority is to increase the awareness of the public regarding the benefits of health insurance, and to increase willingness to pay rate. Bangladesh Journal of Medical Science Vol.17(2) 2018 p.230-237